A kaleidoscope: The role of the social work practitioner and the strength of social work theories and practice in meeting the complex needs of people trafficked and the professionals that work with them. (January 2014) - Busch-Armendariz, Noël; Nsonwu, Maura Busch; Heffron, Laurie Cook
This qualitative research study explored responses to trafficking in persons. Fifty-five ( n = 55) interviews were collected and data were analyzed using qualitative iterative processes. The social worker and the utilization of social work perspectives provided a strong and effective framework for service delivery and effective interdisciplinary collaboration. The ecological, strengths-based, and victim-center approaches were a benefit to survivors and professionals specifically around coordinated efforts, trust-building, and increased cultural competence. Findings also support that individuals who are trafficked have unique needs and social workers' theoretical and practice modalities are well suited to respond to and coordinate these distinct circumstances.